Orbit Space Information System (Sirubit) as Learning Media at PT Orbit Ventura Indonesia - Apriyani, Yanti; Ilham, Robby; Pertiwi, Melisa Winda; Amirulloh, Imam (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The rapid advancement of Information Technology (IT) has made the need for an IT-based teaching and learning concept and procedure inevitable. This concept, widely known as e-learning, has driven a transformation of conventional education into a digital format—both in terms of content and system. Currently, PT Orbit Ventura Indonesia implements a Learning Management System (LMS) to access learning materials, complete, and submit assignments. However, for the Independent Study Program in Cloud Computing, participants also rely on WhatsApp, where mentors deliver learning videos. This leads to an ineffective learning process, as the instructional videos are shared separately through WhatsApp rather than integrated into a unified system. The objective of this study is to develop a simple yet user-friendly video-based Learning Management System. The system is designed as a web-based platform using the CodeIgniter framework, PHP programming language, and MySQL database, with the system development process following the Agile Development Method. As a result, a web-based e-learning platform called Sistem Informasi Ruang Orbit (SIRUBIT) was successfully designed and implemented. This platform is expected to provide both mentors and participants with a more flexible and accessible learning experience—anytime and anywhere.